The Effect of Short and Long Fiber on Impact Strength in High Density Polyethylene-Fiberglass Composite - M Dalil; Elgi Oki Andeska; Dodi Sofyan Arief (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
This study aims to investigate the HDPE (High Density Polyethylene) reinforced with fiberglass to increase strength and toughness into a composite that has the potential to replace ABS (Acronitrile Butadiene Styrene). The composites were made with variations in composition based on volume fraction. The HDPE as matrix and fiberglass as reinforcement through the mixing method, molded in a heating machine (T=140°C), pressed with a pressing time of ±45 minutes. Then, the specimens were cut according to ASTM D6110 standard, and the Charpy impact test was performed. The impact of long fiber for the HDPE composition of 70%vol and fiberglass 30%vol, the average impact strength was 176.838 Joule/mm². The long fiber for the HDPE composition of 80%vol and fiberglass of 20%vol, the average impact strength was 208.08 Joule/mm². The impact of short fiber for HDPE composition of 70%vol and fiberglass of 30%vol, the average impact strength was 72.858 Joule/mm². The short fiber for HDPE composition 80%vol and fiberglass of 20%vol, the average impact strength was 33.394 Joule/mm². Based on research of ABS mixture at 40%/60%vol mixture variation, the average impact strength was 24.8 Joule/mm2 and the 20%/80%vol mixture variation, the impact strength was 18 Joule/mm². In conclusion, the impact strength of the ABS was lower than the HDPE-Fiberglass composite. Therefore, the HDPE-Fiberglass composite can be used as a substitute for ABS for car bumpers.